A molecular model for ion dehydration in confined water. Issue 6 (28th February 2020) - Qing, Leying; Tao, Jiabo; Yu, Hongping; Jiang, Peng; Qiao, Chongzhi; Zhao, Shuangliang; Liu, Honglai
Abstract: Although ion dehydration in confined water is ubiquitous in many important processes concerning ion adsorption, transport and separation, and so forth, few theoretical models have been developed to unravel the mechanism of dehydration in confined space. Herein, a molecular model is proposed by weighing the molecular orientation of surrounding water within the first hydration shell, and then this model is applied to predict the hydration numbers and hydrated radii of simple ions with the help of molecular density functional theory. The predictions are rationalized not only with parallel simulations but also with relevant experimental measurements. We find that the ion hydration in confined water is depressed owing to the confinement, and thus the multilayer hydration shell is disturbed, which results in the decline of hydration number and hydrated radius, favoring the ion dehydration. This work provides an insightful route toward the quantitative understanding and prediction of ion dehydration in confined water.